Can postpartum maternal urinary iodine be used to estimate iodine nutrition status of newborns?. Issue 7 (9th February 2016) - Nazeri, Pantea; Mirmiran, Parvin; Hedayati, Mehdi; Mehrabi, Yadollah; Delshad, Hossein; Azizi, Fereidoun
Abstract: I deficiency can lead to detrimental effects, particularly in neonates and young infants. The aim of this study was to explore whether postpartum maternal urinary I can be used to estimate the I status of newborns. In this cross-sectional study conducted in Tehran, lactating mothers and newborns, within 3–5 d postpartum, were randomly selected. Urine samples were collected from each mother and newborn, and a heel-prick blood sample was obtained from all newborns as part of the routine national newborn screening programme. According to the WHO criteria, median urinary I concentration (UIC) <100 µg/l and frequency over 3 % of thyroid stimulating hormone (TSH) >5 mIU/l was considered as I insufficiency. A total of 147 postpartum women and neonates, aged 27·8 (sd 5·3) years and 4·2 (sd 0·6) d, respectively, completed this study. The median UIC was 68·0 (interquartile range (IQR) 39·4–133·5) and 212·5 (IQR 92·3–307·3) µg/l in postpartum mothers and newborns, respectively. The median neonatal TSH was 1·00 (IQR 0·50–1·70) mIU/l. There was no significant difference in the neonatal UIC and TSH of infants whose mothers had deficient and sufficient urinary I. In the multiple linear regression, neonatal UIC value was associated with maternal urinary I ( P =0·048) and parity ( P =0·039); a significant association was observed between neonatal TSH and infant sex ( P =0·038) and birth weight ( P =0·049). The findings of our study demonstrate that, despite postpartum mothers being mildly I deficient, I status of their infants was adequate as assessed by UIC and TSH values. It seems factors other than maternal urinary I may influence the I status in newborns.